Anxiogenic-like effect induced by TRPV1 receptor activation within the dorsal periaqueductal gray matter in mice - Mascarenhas, Diego Cardozo [UNESP]; Gomes, Karina Santos [UNESP]; Nunes-de-Souza, Ricardo Luiz [UNESP] (Elsevier, 2013)
Pharmacological manipulation of TRPV1 (Transient Receptor Potential Vanilloid type-1) receptors has been emerging as a novel target in the investigation of anxiety states. Here, we attempt to show the role played by the TRPV1 receptors within the dorsal periaqueductal gray matter (dPAG), a midbrain structure strongly involved in the modulation of anxiety. Anxiety was assessed by recording spatiotemporal [percent open arm entries (%OE) and percent open arm time (%OT)] and ethological [e.g., head dipping (HD), stretched-attend postures (SAP)] measures in mice exposed to the elevated plus-maze (EPM). Mice received an intra-dPAG injection of the TRPV1 agonist capsaicin (0, 0.01, 0.1 or 1.0. nmol/0.2. μL; Experiment 1) or antagonist capsazepine (0, 10, 30 or 60. nmol/0.2. μL; Experiment 2), or combined injections of capsazepine (30. nmol) and capsaicin (1.0. nmol) (Experiment 3), and were exposed to the EPM to record spatiotemporal and ethological measures. While capsaicin produced an anxiogenic-like effect (it reduced %OE and %OT and frequency of SAP and HD in the open arms), capsazepine did not change any behavior in the EPM. However, when injected before capsaicin (1.0. nmol), intra-dPAG capsazepine (30. nmol-a dose devoid of intrinsic effects) antagonized completely the anxiogenic-like effect of the TRPV1 agonist. These results suggest that the anxiogenic-like effect produced by capsaicin is primarily due to TRPV1 activation within the dPAG in mice, but that dPAG TRPV1 receptors do not exert a tonic control over defensive behavior in mice exposed to the EPM. © 2013 Elsevier B.V.
Keywords: Anxiety; Capsaicin; Capsazepine; Elevated plus-maze; Mice; Periaqueductal gray matter; capsaicin; capsazepine; vanilloid receptor 1; vanilloid receptor agonist; animal behavior; animal experiment; animal model; animal tissue; anxiety; body posture; ethology; experimental mouse; head movement; histopathology; maze test; mouse; neurologic examination; neuromodulation; nonhuman; periaqueductal gray matter; priority journal; protein function; spatiotemporal analysis